Optimizing the Role of the Legal Aid Post of the Consultation and Legal Aid Institute of the Faculty of Sharia, Antasari State Islamic University in Providing Legal Services For the Community (Study on Several Religious Courts in South and Central Kalima - Nadiyah, Nadiyah; Rahmi, Diana; Sa'adah, Sa'adah (Pascasarjana UIN ANTASARI Banjarmasin, 2022)
This study evaluates the role of Posbakum (Legal Aid Post) at the Faculty of Sharia UIN Antasari in legal services at the Religious Courts in South and Central Kalimantan. Findings indicate that the Posbakum's role is not yet optimal, prompting the LKBH management to propose measures such as enhancing the quality of staff, adjusting the number of staff and salaries, and improving collaboration with relevant stakeholders. Financial constraints and stagnation in collaboration were identified as obstacles, limiting the effectiveness of Posbakum staff. Optimization efforts require additional funding, accreditation, and active collaboration with other organizations. Partnerships are considered a solution for accelerating accreditation and expanding services, emphasizing the importance of financial support, enhanced collaboration, and increased resources to enable Posbakum to play an optimal role in providing legal services to the community.